The incidence of and risk factors for hyperglycemia and hypoglycemia in preterm infants receiving early-aggressive parenteral nutrition - Dina Angelika; Risa Etika; Martono Tri Utomo; Loysa Ladydi; Mahendra Tri Arif Sampurna; Kartika Darma Handayani; I Dewa Gede Ugrasena; Pieter JJ. Sauer (Heliyon, 2023)
Introduction: Optimizing nutritional support helps prevent extra uterine growth restriction and adverse long-term outcomes in preterm infants. Objectives: This study aimed to analyze the incidence of and risk factors for hyperglycemia and hypoglycemia in preterm infants receiving early-aggressive parenteral nutrition (PN). Methods: This prospective observational study included preterm infants receiving PN at the Neonatal Intensive Care Unit of Dr. Soetomo General Hospital between April 2018 and May 2019. Potential risk factors analyzed included asphyxia, sepsis, respiratory distress syndrome, multiple congenital anomalies, mortality, necrotizing enterocolitis, retinopathy of prematurity, the postoperative period, inotropic administration, glucose infusion rate (GIR) > 10–12 mg/kg/min, GIR 4–<5.5 mg/kg/min, and increase in GIR <1 mg/kg/min. Results: Of the 105 preterm infants included, hyperglycemia and hypoglycemia were found in 14 (13.3%) and 26 (24.8%) infants, respectively, with most incidents occurring in the first week (hyperglycemia: 85.7%; hypoglycemia: 88.5%). Sepsis was an independent risk factor for hyperglycemia (odds ratio [OR]: 8.743, 95% confidence interval [CI]: 2.392–31.959; P = 0.001). Hypoglycemia independent risk factors included the postoperative period (OR: 4.425, 95% CI: 1.218–16.073; P = 0.024) and use of GIR 4–<5.5 mg/kg/min (OR: 2.950, 95% CI: 1.035–8.405; P = 0.043). Conclusion: Hyperglycemia and hypoglycemia can occur in preterm infants receiving early-aggressive PN; most cases occur within the first week of life. Hypoglycemia correlated with low glucose intake, and hyperglycemia correlated with sepsis. Monitoring blood glucose levels in preterm infants receiving PN, especially in the first weeks of life, may decrease morbidity associated with hyperglycemia or hypoglycemia.